Adaptation and Continuation Born from Our Non-Recognition of Abandonment - Constantin Tovarnițchii (Symbolon, 2022)
The explanatory dictionary of the Romanian language defines art as „an activity of man that aims to produce aesthetic values and that uses means of expression with a specific character; all the works (from an era, from a country, etc.) that belong to this activity”. Looking back, we find that, regardless of the era we are focusing on, art, as a whole, has not known downtime, despite any unfavourable conditions of a social or economic nature. On the contrary, when major crisis situations took over society, art experienced a revival in almost all its forms of expression.